2021
DOI: 10.1155/2021/5530898
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Traditional Chinese Medicine in Relieving EGFR-TKI-Associated Diarrhea Based on Network Pharmacology and Data Mining

Abstract: In this study, the role of traditional Chinese medicine (TCM) in relieving epidermal growth factor receptor-tyrosine kinase inhibitor- (EGFR-TKI-) associated diarrhea was discussed by network pharmacology and data mining. Prediction of drug targets by introducing the EGFR-TKI molecular structures into the SwissTargetPrediction platform and diarrhea-related targets in the DrugBank, GeneCards, DisGeNET, and OMIM databases were obtained. Compounds in the drug-disease target intersection were screened by absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…It can effectively improve TCM syndrome scores, and the adverse reactions are slight. 22 This study further analyzed the publication bias of the included literature, and the results showed that there was a certain bias in the comparison of TCM syndrome scores between the two groups. In view of these results, it is suggested that using different test methods to observe the bias of the unified index in the future will improve the credibility of the literature.…”
Section: Discussionmentioning
confidence: 97%
“…It can effectively improve TCM syndrome scores, and the adverse reactions are slight. 22 This study further analyzed the publication bias of the included literature, and the results showed that there was a certain bias in the comparison of TCM syndrome scores between the two groups. In view of these results, it is suggested that using different test methods to observe the bias of the unified index in the future will improve the credibility of the literature.…”
Section: Discussionmentioning
confidence: 97%
“…The active compounds and their corresponding targets were screened using Traditional Chinese Medicine Systems Pharmacology (TCMSP) ( , accessed on 15 June 2023), SwissADME ( , accessed on 15 June 2023), and SwissTargetPrediction Database ( , accessed on 15 June 2023), following previously reported methods [ 105 ]. The targets of the ingredients were standardized using the UniProt database ( , accessed on 18 June 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Potential target genes of CP were collected from Online Mendelian Inheritance in Man (OMIM) ( https://omim.org/ ), 25 DrugBank Online ( https://www.drugbank.ca/ ), 26 DisGeNT database ( https://www.disgenet.org/ ), 26 and Genetic Association Database (GAD) ( https://geneticassociationdb.nih.gov/ ) 25 with the keyword of “chronic pharyngitis”. The overlapping and repeat targets were excluded.…”
Section: Methodsmentioning
confidence: 99%